Uncertainty in end-point tension measurement in wires subject to high-velocity impact - Da Forno, R.; Saggin, B. (Measurement : journal of the International Measurement Confederation, 1995)
This paper analyses sensor performance requirements in measuring end-point tension (in magnitude and direction) in cables subject to high-velocity impact. The work may be viewed as a tool to analyse and design end-point tension measurement devices for cable-like systems when wire dynamics is very rapid (> 10 kHz) and fully non-linear. Load effect, conversion time and ADC quantization effects are analysed in order to provide a full description of these uncertainty sources by simultaneous integration of the set of hyperbolic partial differential equations governing cable motion, and the set of ordinary differential equations describing the motion of the impacting object and sensor dynamics. Three-dimensional mathematical modelling of the wire is based on the theory of quasi-linear partial differential equations. Fully non-linear analysis of wire motion is thus accomplished without restrictions on displacement and deformation magnitudes. Numerical solution algorithms are based on the characteristics method. The main result is that the dynamic error due to sensor dynamics is the principal source of uncertainty. Moreover, the reduction of such uncertainty is not allowed by the actual force transducer devices, due to the high frequency response required.